2016
DOI: 10.1021/acs.jpclett.6b01365
|View full text |Cite
|
Sign up to set email alerts
|

Physics behind Water Transport through Nanoporous Boron Nitride and Graphene

Abstract: In this work, molecular dynamics simulations were used to determine the surface tension profile of water on graphene and boron nitride (BN) multilayers and to predict water permeation through nanoporous graphene and BN membranes. For both graphene and BN multilayers, a decrease in surface tension (γ) was evidenced as the number of layers increased. This lessening in γ was shown to result from a negative surface tension contribution due to long-range wetting of water, which also contributes to lower water perme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
78
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 82 publications
(83 citation statements)
references
References 26 publications
5
78
0
Order By: Relevance
“…As shown in Figure 3, N W tends to level off after 5–8 ns as a result of the finite size of the high‐pressure reservoir. Figure shows the salt rejection R (defined as R=1CNaCloutletCNaClinlet, where C NaCl is the salt (NaCl) concentration) as a function of the water permeability P W for the four MWCNT as well as fully aromatic polyamide and sub‐nanoporous boron nitride (hBN) membranes (it has recently been shown that the water permeability of sub‐nanoporous hBN membranes can exceed that of nanoporous graphene [ 26,67 ] ). Water permeability accounts for both the surface area crossed by the water molecules ( A ) and the membrane thickness (Lz) and was defined as PnormalW=NnormalW·LZAΔP·t·1.076·103 (unit: kg m m −2 bar −1 h −1 ).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…As shown in Figure 3, N W tends to level off after 5–8 ns as a result of the finite size of the high‐pressure reservoir. Figure shows the salt rejection R (defined as R=1CNaCloutletCNaClinlet, where C NaCl is the salt (NaCl) concentration) as a function of the water permeability P W for the four MWCNT as well as fully aromatic polyamide and sub‐nanoporous boron nitride (hBN) membranes (it has recently been shown that the water permeability of sub‐nanoporous hBN membranes can exceed that of nanoporous graphene [ 26,67 ] ). Water permeability accounts for both the surface area crossed by the water molecules ( A ) and the membrane thickness (Lz) and was defined as PnormalW=NnormalW·LZAΔP·t·1.076·103 (unit: kg m m −2 bar −1 h −1 ).…”
Section: Resultsmentioning
confidence: 99%
“…In a recent work, Garnier et al have shown that water permeation through subnanoporous boron nitride (sNBN) monolayers could even be faster than through nanoporous graphene, thus heralding boron nitride as a potential candidate for the next generation of nanofilters. [26] As mentioned previously, CNTs have demonstrated very interesting transport performance in terms of both water permeability and salt rejection. Among the different CNT materials, single-walled CNTs have been largely investigated as potential RO membranes while multi-walled CNTs (MWCNTs) have much less been considered for RO applications.…”
Section: Introductionmentioning
confidence: 84%
See 3 more Smart Citations